EFL students’ ability in writing reviews for a novel at a university in Medan - Yenita Uswar; Nova Andriani (Universitas Syiah Kuala, 2019)
This research aimed at investigating the ability of the fourth semester English Education Department students at the University of Potensi Utama, Medan, in writing a review text of a novel entitled ‘Sengsara Membawa Nikmat’ written by Toelis Soetan Sati. This study applied a qualitative approach through writing tests as the data collection instrument. The data were, furthermore, analyzed by identifying and evaluating the students’ writing test. The result reveals that overall, the students’ review texts on the novel were good enough. However, some problems were still noticed in the students’ texts such as the errors in vocabulary, grammar, generic structure, organizing ideas, mechanic (punctuation and spelling) and the summary of the novel. It implies that while the students’ performance was generally satisfying, their ability to write a review text needs to be consistently improved to produce a better piece of a review text on a novel.